Social Capital Construction in Informal Strategic Alliances in Micro Enterprises: The Role of MSME (Micro, Small, and Medium Enterprises) Companions as External Facilitators - Bisma Widyawan; Dhani Salman; Indah Wahyu Maesarini (Journal of Business, Social and Technology, 2026)
Background: Micro businesses have been recognised globally for their contribution to wealth and job creation, but they continue to face sustainability challenges due to limited resources, networks, and managerial capacity. An approach to overcome these limitations is to create informal strategic alliances through collaborative efforts. Most studies, however, assume that social capital in business networks evolves naturally, thus overlooking the role of external facilitation in intentionally constructing social capital, especially in the context of developing countries with the proliferation of micro-enterprises. Objective: The purpose of this study is to examine the social construction process of social capital in informal strategic alliances in microenterprises, with particular attention to the role of MSME companions as external facilitators. Methods: A qualitative approach with a case study design focusing on the Gerai Jajanan Turki (GJT) community in Depok City. A combination of methods was used to collect data, including semi-structured interviews with business actors and customers, a survey, and document analysis. NVivo 15 was used for thematic analysis. Results: This research found that informal alliances and social capital were constructed in GJT through the facilitation of MSME companions. Companions aided in establishing connections between business actors and assisted in communication, role allocation, and dispute resolution, resulting in partnerships replete with trust and stable business alliances. Conclusion: The construction of collaborative networks can be facilitated by external facilitators. This study builds upon the social capital construction framework by proposing that trust and cooperative norms may be purposefully created through facilitative means.